Question of the integrity of the ondratice l/želeč surface collection - Mlejnek, Ondřej; Škrdla, Petr; Tostevin, Gilbert B.; Lisá, Lenka; Novák, Jan (Römisch-Germanischen Zentralmuseums, 2016)
Excavations during 2010-2012 produced a new early Upper Palaeolithic site Želeč I in Central Moravia. Three settlement horizons were distinguished at this site. The oldest one, predating the cold HE 4, dated by 14C AMS to 42-45 ky BP cal, relates to the main cultural layer in the largest trench Zel_4a with three hearths. The younger horizon, which was dated to 36 ky BP cal, is represented by one soliflucted hearth in the trench Zel_12b and the youngest settlement episode represented by a feature of unknown function in the trench Zel_12a, was dated by 14C AMS to 34 ky BP cal. The existence of three occupational events at the site supports the claim that a collection of surface finds from a neighbouring site Ondratice I / Želeč presents a mixture of lithic assemblages coming from different cultural layers.
Keywords: Czech Republic; Moravia; Palaeolithic; Bohunician; Szeletian; Aurignacian; stratigraphy